2016
DOI: 10.1016/j.measurement.2016.03.048
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of static precise point positioning using GPS only, GLONASS only, and GPS plus GLONASS

Abstract: Abstract:The aim of this paper is to look into the achievable repeatability and accuracy from Precise Point Positioning (PPP) daily solutions when using GPS only (PPP GPS), GLONASS only (PPP GLO), and GPS plus GLONASS (PPP GPS+GLO) for static positioning. As part of the assessment, a comparison with global double difference (DD) GPS daily solutions is presented. It is shown, therefore, that all of the PPP daily solutions can achieve millimetric level repeatability, similar to the global DD GPS solutions. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Numerous investigations have demonstrated that a multi-GNSS approach (e.g., GPS + BeiDou) is able to improve the performance of real-time-kinematic (RTK) positioning, particularly in urban and mountainous areas, where the lack of visible GPS satellite numbers and multipath reflections limit the performance of RTK [55][56][57][58][59]. However, it has been reported that multi-GNSS observations do not noticeably improve the accuracy of static positioning compared to GPS-only observations; somehow, using multi-GNSS observations can even degrade the accuracy of static positioning compared to using GPS-only observations [60][61][62]. Accordingly, we processed GPS and BeiDou observations separately in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have demonstrated that a multi-GNSS approach (e.g., GPS + BeiDou) is able to improve the performance of real-time-kinematic (RTK) positioning, particularly in urban and mountainous areas, where the lack of visible GPS satellite numbers and multipath reflections limit the performance of RTK [55][56][57][58][59]. However, it has been reported that multi-GNSS observations do not noticeably improve the accuracy of static positioning compared to GPS-only observations; somehow, using multi-GNSS observations can even degrade the accuracy of static positioning compared to using GPS-only observations [60][61][62]. Accordingly, we processed GPS and BeiDou observations separately in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is capable of processing L1 and L2 GPS data. It implements an Extended Kalman Filter for positioning employing double differences observables [ 28 ]. The hydrostatic component of the ZTD is calculated using a model such as Saastamoinen, Hopfield or IFADIS and the Neill mapping function.…”
Section: Methodsmentioning
confidence: 99%
“…PPP results using 24-hour observations are characterized by millimetre accuracy, both in the integer ambiguity of phase measurements determination as well as in the float solution variants. The results obtained in different studies prove (Alkan and Öcalan, 2013;Mohammed et al, 2016) that in the case of short, sub-hours sessions this accuracy significantly falls. This part of the paper contains analysis regarding the impact of updating PCC models on a sub-daily derived position component time series.…”
Section: The Position Component Differences In Sub-daily Observation mentioning
confidence: 52%
“…The time series of coordinates were derived from the GNSS observations processing using the precise point positioning (PPP) technique. The advantages and limitations of PPP positioning have been described, among others, in Kouba and Héroux (2001), El-Mowafy (2011), Rizos et al (2012), Alkan and Öcalan (2013), Yigit et al (2013) and Mohammed et al (2016).…”
Section: Introductionmentioning
confidence: 99%